ANTI BULLYING PROJECT “STOP BULLYING EVERYWHERE, EVERY TIME, AND FOR EVERYONE ” TO STRENGTHEN THE PANCASILA STUDENT PROFILE - Yulianti Yulianti; Maulana Fajar Wandhiro; Endang Setyaningsih (Widya Mandala Surabaya Catholic University, 2023)
The limited understanding of teachers in implementing the project method in strengthening the profile of Pancasila students has an impact on the implementation of learning in class. The impact that occurs in the classroom is the lack of formation of the character profile of Pancasila students such as mutual cooperation and global diversity. This study aims to describe the project